Sub-severe hail: the missing piece in assessing asphalt shingle risk in North America - Meisenzahl, Brenna; Giammanco, Ian; Hedayati, Faraz (Frontiers in Materials, 2025)
Hail risk is a growing problem for homeowners and insurers, particularly as insurance claims analysis reveal that asphalt shingle roofs are sustaining damage from hailstone sizes previously thought not to affect most roofing materials. Research by the Insurance Institute for Business and Home Safety indicates that sub-severe hail falls more frequently than large hail, leading the authors to believe that the cumulative damage from repeated sub-severe exposure is much higher than previously expected. To investigate this hypothesis, observations of these types of hail events were applied to conduct laboratory testing of asphalt shingles. A high concentration, sub-severe hail event was recreated in a controlled laboratory setting and used multiple times to test both experimental and control asphalt shingle test specimens, followed by exposure to a large hail event. The experimental group was exposed to natural weathering between sub-severe hail exposures to reflect real-world aging conditions. Both groups were compared to the new product performance against only large hail impacts (baseline)—image processing techniques allowed for the evaluation of damage and quantitative granule loss measurements. The results showed that exposure to high concentrations of small hailstones can significantly reduce the roof cover’s resistance to future large hail events and exacerbate the natural aging of asphalt shingles. This suggests that frequent sub-severe hailstorms may pose a greater threat to roof longevity than previously recognized and is a driving factor in the growing hail risk in the United States that is not accounted for in current durability standards or risk assessments.